The propagation of ocean waves and tsunami - Silveira, Fernando Lang da (2005)
The propagation of ocean waves, particularly of the tsunami, is analyzed in this paper. We show that, starting from some basic results of the theory, many important qualitative and practical features can be understood and predicted.